Changes in the symptoms and quality of life of women with symptomatic pelvic organ prolapse fitted with a ring with support pessary. (November 2018) - Mao, Meng; Ai, Fangfang; Zhang, Ye; Kang, Jia; Liang, Shuo; Xu, Tao; Zhu, Lan
Highlights: Fitting with a ring with support pessary is a safe and effective conservative treatment for pelvic organ prolapse. Almost all of the prolapse symptoms and most of the urinary symptoms were resolved in the women in this study. The health-related quality of life of the women significantly improved. The effects on defecatory symptoms were limited. Abstract: Objectives: The study aim was to assess the effect of treatment with a ring with support pessary on bothersome symptoms and the quality of life of patients with symptomatic pelvic organ prolapse (POP). Study design: In this prospective observational study, 142 patients with symptomatic POP were successfully fitted with a ring with support pessary between November 2015 and November 2016 and followed up until December 2017. Prolapse and urinary symptoms were assessed, and the Pelvic Floor Distress Inventory-20 (PFDI-20) and Pelvic Floor Impact Questionnaire-7 (PFIQ-7) were administered at baseline and at each follow-up visit. Univariate analyses, McNemar's test and paired t-tests were used for data analyses. Main outcome measures: Changes in prolapse and urinary symptoms and quality of life after fitting with a ring with support pessary use. Results: The median (range) duration of follow-up was 17 (13–24) months. At the study endpoint, 98 patients (74.8%) continued to use the pessaries. Wider vaginal introitus (≥5 cm) was found to be a predictor of pessary discontinuation. Although de novo stress urinary incontinence occurred in 27.1% of patients, almost all prolapse symptoms and most of the concurrent urinary symptoms were resolved, with voiding difficulty resolved most significantly. Scores on both the PFIQ-7 and PFDI-20 had significantly improved at the study endpoint, with changes in scores on the urinary and prolapse sub-scales of both questionnaires demonstrating clinical significance (effect size>0.5). Conclusions: A ring with support pessary is a safe and effective conservative treatment for POP; it not only relieves bothersome prolapse and urinary symptoms but also significantly decreases their impacts on health-related quality of life. However, the method has a limited effect on defecatory symptoms.